Evaluation of Vomitoxin Control Strategies on Nursery Pig Growth Performance and Blood Measures - Larissa L. Becker; Jordan T. Gebhardt; Mike D. Tokach; Robert D. Goodband; Joel M DeRouchey; Jason C. Woodworth; Arnau Vidal; Christos Gougoulias (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 4,318 pigs (337 × 1050, PIC; initially 14.3 ± 0.18 lb) were used in a 35-d growth trial to evaluate mycotoxin control strategies on nursery pig performance and blood measures. Pigs were weaned at approximately 21 d of age and randomly allotted to 1 of 5 dietary treatments. The randomized complete block design was blocking structure including sow farm origin, date of entry into the facility, and average pen BW. A total of 160 pens were used with 80 double-sided 5-hole stainless steel fence line feeders, with feeder serving as the experimental unit. For each feeder, 1 pen contained 27 gilts and 1 pen contained 27 barrows. There were 16 replications per dietary treatment. A common phase 1 diet was fed in pelleted form to all pigs for 7 d prior to treatment diets. Experimental treatments were fed in a single phase and included a 1) low deoxynivalenol (DON) diet; 2) high DON diet; 3) high DON + sodium metabisulfite (SMB); 4) high DON + Technology1; or 5) high DON + Technology1+. Overall (d 0 to 35), pigs fed the high DON diet had reduced (P<0.001) ADG, ADFI, and final BW compared to the pigs fed the low DON diet. Furthermore, pigs fed the high DON+SMB diet had greater (P<0.05) ADG, ADFI, and final BW compared to the pigs fed the high DON, high DON+Technology1, or high DON+Technology1+ diets. An improvement (P<0.05) in feed efficiency was observed in pigs fed high DON+SMB or high DON+Technology1+ diets compared to the low DON or high DON+Technology1 diets with high DON diets intermediate. Pigs fed high DON+SMB or high DON+Technology1 diets had reduced (P<0.05) total removals and mortality compared to pigs fed low DON diets with high DON and high DON+Technology1+ intermediate. For economic analysis (d 0 to 35), pigs fed high DON+SMB diets had the greatest (P<0.05) feed cost, revenue, and IOFC compared to all other treatments. The LC-MS/MS analysis of dried blood spots at the end of the trial revealed that pigs fed high DON or high DON+Technology1 had increased (P<0.05) DON concentrations in the blood compared to low DON, with high DON+SMB and high DON+Technology1+ intermediate. Interestingly, while not statistically significant in this study, the reductions in presence and concentration of other important mycotoxins like fumonisin B1, B2, beta-zearalenol, and the emerging beauvericin—as well as the trends in circulating neutrophil-to-lymphocyte ratio and GGT in blood—when pigs were fed high DON+Technology1+ suggest that other important metabolic processes may be influenced. In summary, pigs fed high DON diets had reduced performance compared to pigs fed low DON diets. In our trial, SMB supplementation to high DON diets led to the greatest improvement in growth performance, but other metabolic changes associated with Technology1+ warrant further investigation.
Keywords: Deoxynivalenol; mycotoxin; nursery pigs; sodium metabisulfite